Overcoming Stunting in Children with VCO-prebiotic as a Nutritional Supplement with Housewives from the DASHAT Program - Armaini; Sumaryati Syukur; Rahmiana Zein; Yetria Rilda; Upita Septiani; Tio Putra Wendari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Stunting in children is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, especially in the first 1,000 days of life. The prevalence of stunted children in West Sumatra is 25.2%, and in Padang City it is 19.5%, which shows a high stunting rate in Padang City. The Community service activities empower housewives to produce VCO with prebiotics as a nutritional supplement for stunted children in Bukik Karan Rawang Village, Padang City. Providing VCO supplements that contain good fats, prebiotics, and antioxidants improves children's digestive systems, increases their immunity, prevents them from infectious diseases, and supports the development of their brains and nervous systems. Technology transfer provides skills for mothers of stunted children to make their own VCO, and can also improve the family economy. The growth and development of stunted children improve, as indicated by measurable parameters such as increased height and weight, after they are given VCO with prebiotics. Weight gain between 1-1.8 kg, an average of 1.47 kg, and height between 2.2-7 cm, an average of 4.38 cm in stunted children. Education on diet and Parenting Patterns for stunted children is carried out by providing knowledge, training, nutritional counseling, and parenting to increase insight among mothers of stunted children about nutrition supplements and healthy and nutritious foods to achieve improved health. Providing VCO with prebiotics can enhance children's growth and development and improve their nutritional status to help overcome stunting.